2022
DOI: 10.7554/elife.74270
|View full text |Cite
|
Sign up to set email alerts
|

KLC4 shapes axon arbors during development and mediates adult behavior

Abstract: Development of elaborate and polarized neuronal morphology requires precisely regulated transport of cellular cargos by motor proteins such as kinesin-1. Kinesin-1 has numerous cellular cargos which must be delivered to unique neuronal compartments. The process by which this motor selectively transports and delivers cargo to regulate neuronal morphogenesis is poorly understood, although the cargo-binding kinesin light chain (KLC) subunits contribute to specificity. Our work implicates one such subunit, KLC4, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…Future studies with finer temporal precision are needed to test whether these protrusions aid in recruiting afferent terminals to form kylikes. Live-cell imaging of zebrafish embryos has also been used to study development of peripheral axon arbors in Rohon Beard cells, a population of gentle-touch neurons that transiently exist during development and are responsible for initiating escape responses (Clarke et al, 1984; Haynes et al, 2022). Recent work has shown that peripheral arborization of Rohon Beard cells depends on kinesin light chain 4 (Haynes et al, 2022), which regulates binding between cellular cargo and kinesin motors (Morfini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Future studies with finer temporal precision are needed to test whether these protrusions aid in recruiting afferent terminals to form kylikes. Live-cell imaging of zebrafish embryos has also been used to study development of peripheral axon arbors in Rohon Beard cells, a population of gentle-touch neurons that transiently exist during development and are responsible for initiating escape responses (Clarke et al, 1984; Haynes et al, 2022). Recent work has shown that peripheral arborization of Rohon Beard cells depends on kinesin light chain 4 (Haynes et al, 2022), which regulates binding between cellular cargo and kinesin motors (Morfini et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Live-cell imaging of zebrafish embryos has also been used to study development of peripheral axon arbors in Rohon Beard cells, a population of gentle-touch neurons that transiently exist during development and are responsible for initiating escape responses (Clarke et al, 1984; Haynes et al, 2022). Recent work has shown that peripheral arborization of Rohon Beard cells depends on kinesin light chain 4 (Haynes et al, 2022), which regulates binding between cellular cargo and kinesin motors (Morfini et al, 2016). In the absence of KLC4, new branches initiate but do not properly separate from sister branches, which ultimately results in abnormal axon fasciculation (Haynes et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(iii) KIFBP mutations are disruptive to axonal MT bundles and cause Goldberg-Shprintzen syndrome (‘GOSHS’ in Supplementary Table S1 A ; Lyons et al, 2008 ; Hirst et al, 2017 ; Chang et al, 2019 ). (iv) KLC mutations are linked to HSP/SPG and SPOAN ( Supplementary Table S1 A ; Bayrakli et al, 2015 ; Melo et al, 2015 ; Fu et al, 2021 ; Gümüşderelioğlu et al, 2023 ) and to excessive axon branching in zebrafish ( Haynes et al, 2022 ).…”
Section: Links Of Axonal Transport To Axonal Disordersmentioning
confidence: 99%